Shrinkage of Biocomposite Material Specimens [HA/Bioplastic/Serisin] Printed using a 3D Printer using the Taguchi Method - Felix Krisna Aji Nugraha (International Journal of Applied Sciences and Smart Technologies, 2022)
The Fused Deposition Modeling method in the rapid prototyping technique was modified using a paste-shaped material with biocomposite material. One of the correction factors for the printed test specimen results is shrinkage. The paste material used is hydroxyapatite [CA5(PO4)6(OH)2] and tapioca bioplastic is one of the biomaterials that has been widely used in tissue engineering. Besides these materials, sericin is added, which is produced from extracts from silkworm cocoons.The composition of the biocomposite paste used with the ratio of hydroxy apatite and bioplastic was 40:50, 50:50, 60:40, by adding 0.3% sericin to the hydroxyapatite solution. The parameters used in the printing process of the test specimens are the perimeter speed of 60 mm/s, the infill speed of 10 mm/s, and the layer height of 0.45 mm. The design in this test has dimensions of 100mm long, 25mm wide, and 3mm thick. The optimal shrinkage of the test specimens was analyzed using the Taguchi . methodSpecimen printing is done by using additive manufacturing method. The process is carried out using a Portabee three-dimensional printing machine that uses a Fused Deposition Modeling (FDM) system modified to an Aqueous-Based Extrusion Fabrication (ABEF) system. The size of the printed test specimens with dimensions of 100mm long, 25mm wide, and 3mm thick. The comparison of the biocomposite materials used in the composition of hydroxyapatite suspension paste and tapioca starch bioplastics ranged from 40:50, 50:50, 60:40, with the addition of 0.3% sericin hydroxyapatite suspension. The optimal composition of the bioplastic material was analyzed using the method. Taguchi.The results obtained that the optimum composition for shrinkage of the hydroxyapatite and bioplastic compositions was 50:50 with the addition of 0.3% sericin to the hydroxyapatite solution